(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The poet sends blessings and peace to the Messenger of Allah. Because, in a number of religious and mystical sources, the virtue of sending blessings to the Messenger of Allah is mentioned. For example, “The Messenger of Allah, may Allah bless him and grant him peace, said: “The closest of you to me in Paradise are those who send blessings on me the most. So increase your blessings on me during the bright night and the bright day.” Therefore, the poet says, O Messenger of Allah, may Allah bless you with a thousand blessings from the Owner of Majesty and Honor (Allah). The quote in the verse “Bika min zil-jaloli wal-ikram” is taken from verses 26-27 of Surah “Ar-Rahman”: “All that is on the face of the earth is perishable. Your Lord, the Owner of Majesty and Honor, is eternal.”